ANALISIS FEMINISME INTERSEKSIONAL DALAM NOVEL SEBONGKAH TANAH RETAK KARYA RIDA FITRIA - Mulahaeri; Irna Fitriana; Muhammad Asdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the representation of migrant women characters in the novel Sebongkah Tanah Retak by Rida Fitria through the perspective of intersectional feminism. The study employs a descriptive qualitative approach with an intersectional feminist literary analysis. The primary data consist of the novel text, while secondary data are obtained from relevant books, journals, and scholarly articles. Data collection is conducted through library research by reading, examining, and noting sections that represent the experiences of migrant women characters. Data analysis uses a thematic content analysis model by identifying patterns of representation based on intersectionality categories. Data validity is strengthened through triangulation of theories and literature sources. The results indicate that migrant women characters are represented in a complex and multidimensional manner, particularly through the experiences of the character Ijah. This representation reveals the close interconnection between gender identity, migrant worker status, and socio-economic conditions that intersect with one another. From an intersectional feminist perspective, Ijah’s experiences reflect how these overlapping identities shape a life marked by vulnerability while simultaneously illustrating women’s subordinate position within social structures. Migrant women characters are portrayed not only as victims but also as subjects who possess awareness of the situations they face. This representation emphasizes that the experiences of migrant women cannot be understood in a singular way, but rather must be seen as the result of interactions among various social factors that produce complex forms of inequality.